The Effect of Feeding Acidifier and Probiotics with Different Levels in The Diet Growth on Broiler Performance - Fita Ridhana; Rahmawati Rahmawati; Ali Makmur (UNIVERSITAS ISLAM LAMONGAN, 2021)
This research which aims to determine the effect of probiotic and Acidifier supplementations in the fermentation diet on growth of broiler has done in Takengon, Central Aceh District from August until October 2020. This research used 160 chicks strain Cobb 89 produced by PT. Charoen Pokphand. This study used a complete randomized design consisting of 4 treatments and 4 replications. The treatment of probiotic and Acidifier supplementations were: 0% (A), 0.1% (B), 0.2%(C), 0.3%(D). Parameters observed were achievement of final weight, weight gain, feed consumption, feed conversion, and feed efficiency. Data was analyzed by analysis of variance (ANOVA) and continued by Duncan Multiple Range Test if significant effect was detected. The result showed that the differences in supplementation of probiotic and Acidifiers effected significantly (P <0.05) on the final weight, weight gain, feed conversion and feed efficiency. However, there was no significant effect on rate of consumption. The result of present study showed that the combination of probiotic and Acidifier had a best impact on broiler growth and it was also decreased mortality of chicken.